2017
DOI: 10.21804/20-1-1358
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of urban and rural patients with chronic kidney disease referred to Inkosi Albert Luthuli Central Hospital in Durban, South Africa

Abstract: Background: The profiles of patients with chronic kidney disease (CKD) in rural areas have long been thought to differ from those of their urban counterparts. However, there have been few local studies to confirm this. Methods: A retrospective review was conducted to compare the characteristics of patients with CKD from rural and urban areas in the South African province of KwaZulu-Natal, who were referred to Inkosi Albert Luthuli Central Hospital (IALCH) from April 2012 to April 2013. Results: A total of 529 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A similar study from the Canadian Organ Replacement Registry reported higher overall mortality and deaths from infectious causes among HD patients who lived farther from their attending nephrologist [ 27 ]. Developing countries such as South Africa are likely to have a greater proportion of remote or rural patients requiring RRT [ 28 ]. A recent study comparing rural and urban South African CKD patients attending a tertiary hospital in the province of KwaZulu-Natal found that rural patients presented with more advanced renal disease and had higher rates of HIV infection [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study from the Canadian Organ Replacement Registry reported higher overall mortality and deaths from infectious causes among HD patients who lived farther from their attending nephrologist [ 27 ]. Developing countries such as South Africa are likely to have a greater proportion of remote or rural patients requiring RRT [ 28 ]. A recent study comparing rural and urban South African CKD patients attending a tertiary hospital in the province of KwaZulu-Natal found that rural patients presented with more advanced renal disease and had higher rates of HIV infection [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Developing countries such as South Africa are likely to have a greater proportion of remote or rural patients requiring RRT [ 28 ]. A recent study comparing rural and urban South African CKD patients attending a tertiary hospital in the province of KwaZulu-Natal found that rural patients presented with more advanced renal disease and had higher rates of HIV infection [ 28 ]. Another South African study, at a private–public dialysis centre in Limpopo, found rural dwelling to be associated with higher all-cause mortality in patients treated with continuous ambulatory peritoneal dialysis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, current knowledge about the prevalence of CKD and renal disease in Malawi, as in most sSA countries, is scarce 9 . Published data on CKD have been based on opportunistic sampling, involving people seeking medical care, or of urban populations, who have a different epidemiological profile from the rural majority 6, 10 . It is thought that glomerulonephritis and CKD of unknown origin (CKDu), might account for a larger proportion of the total CKD burden in rural or disadvantaged populations, whilst hypertension and diabetes are more prevalent in urban areas 3, 11 .…”
Section: Introductionmentioning
confidence: 99%